Pooled analysis of 1‐year recall data from three root canal treatment outcome studies undertaken using cone beam computed tomography. (27th September 2017) - Al‐Nuaimi, N.; Patel, S.; Davies, A.; Bakhsh, A.; Foschi, F.; Mannocci, F.
Abstract: Aim: To provide an estimate of the proportion of successful outcomes of primary and secondary root canal treatments (retreatments) determined by periapical radiographs and cone beam computed tomography (CBCT), a pooled analysis of the data collected from three previous prospective clinical outcome studies was undertaken. Methodology: The analysis pooled the 1‐year results for 354 teeth, including 123 primary treatments and 231 retreatments. All root canals were instrumented with ProTaper Universal and filled using a warm vertical condensation technique. Comparisons of favourable results between root canal treatments and retreatments and between different tooth types were made using chi‐square/Fisher's exact test. Results: The overall percentage of favourable results was 91% using periapical radiographs and 80% for CBCT ( P < 0.001). With CBCT, the percentage of favourable results for primary treatments (84.7%) was not significantly different ( P = 0.316) from that of retreatments (77.9%). When assessed by tooth group, the overall percentage of favourable results with CBCT was 75.5%, 90.6% and 91.1% for molar, premolar and anterior teeth, respectively. When CBCT is used to assess the outcome, the proportion of favourable outcomes in molars was significantly lower than that of premolars and anterior teeth ( P < 0.05). Teeth with root fillings terminating more than 2 mm short of the radiographic apex had less favourable outcomes (73%) compared to long (83%) and adequate root filling length (84%). Conclusions: The proportions of favourable outcomes of primary root canal treatments and retreatments assessed with CBCT were lower when compared to periapical radiographs, and also lower than those historically reported by periapical radiograph‐based outcome studies. Considering the very high favourable outcome of anterior teeth and premolars compared to molar teeth, future studies assessing the effect of new materials and techniques on the outcome of root canal treatments should be based on preoperative and postoperative CBCT images, and focus on molar teeth.